HUBUNGAN DUKUNGAN KELUARGA DENGAN KEMANDIRIAN LANSIA DALAM MELAKUKAN ADL DI DESA TUNTUNGAN II WILAYAH KERJA PUSKESMAS PANCUR BATU KABUPATEN DELI SERDANG - Nagoklan Simbolon; Pomarida Simbolon; Joice Panjaitan (STIKes Santa Elisabeth Medan, 2020)
Introduction. The age of life expectancy of Indonesian women is 74 years old, male 69 year, average life expectancy of 71.2 years (BPS, 2019). United Nations Data shows the number of elderly 2017 is 7.511 billion. Data World Bank, (2019) The number of elderly 5 ASEAN countries in the order as follows Thailand 11.9%, Singapore 11.5%, Vietnam 7.3%, Malaysia 6.7%, and Indonesia 5.7% while in the world 8.9%. Year 2019, the number of Indonesian elderly is prediction to be 27.5 million or 10.3%, year 2020 reached 28.8 million or 11.34% of the total population and 57 million (17.9%) Year 2045 (BPS, 2018). The UN predition that the percentage of Indonesian seniors reached 25 percent in 2050, about 74 million elderly. This figure is a challenge in creating a healthy and productive elderly or independent. Increasing age will add to the family burden. This condition requires the family to support the elderly to remain healthy, so that the self-reliant in conducting ADL. Healthy, active and independent elderly will add to the welfare and happiness of the family. The purpose of research is to know the family support relationship with elderly independence conducting ADL in Tuntungan village II work area Pancur Batu Puskesmas Regency Deli SerdangMethod. This research uses cross sectional methods. Population is all the elderly village of Tuntungan II work area Pancur Batu Public Health Center as much as 299 people. Large samples in research as much as 73 people. Data collection using interview techniques with questionnaires. Research is analyzed by univariate and Bivariat.Result. The results showed a significant relationship between the family support and elderly independence, p value, 0.000.Duscussion. Pancur Batu Public Health Center are advised to provide health education to the family the importance of providing support to theelderly to improve elderly independen